2006
DOI: 10.3168/jds.s0022-0302(06)72113-0
|View full text |Cite
|
Sign up to set email alerts
|

Flavor Profiles of Full-Fat and Reduced-Fat Cheese and Cheese Fat Made from Aged Cheddar with the Fat Removed Using a Novel Process

Abstract: Many consumers are concerned with fat intake. However, many reduced-fat foods, including reduced-fat cheese, lack robust flavors. The objectives of this study were to characterize the flavors found in full-fat cheese, cheese fat, and reduced-fat cheese made from aged Cheddar using a novel process to remove the fat (Nelson and Barbano, 2004). Two full-fat, aged cheeses (9 and 39 mo) were selected, and the fat was removed using the novel fat removal process. Full-fat cheeses, shredded and reformed full-fat chees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 38 publications
4
39
0
Order By: Relevance
“…This is due to the role of fat in providing a medium for the dissolution of flavour compounds and the inhibition of certain enzymatic reactions essential for the formation of flavours (Banks 2004). Lowered levels of fatty acids such as butanoic and hexanoic acids and methyl ketones, as well as increased levels of other compounds, have been attributed to the atypical flavour in low-fat Cheddar cheese (Carunchia-Whetstine et al 2006). They found that flavour profiles of FFC and the same FFC with the fat removed after ripening were almost identical.…”
Section: Description Profilementioning
confidence: 97%
“…This is due to the role of fat in providing a medium for the dissolution of flavour compounds and the inhibition of certain enzymatic reactions essential for the formation of flavours (Banks 2004). Lowered levels of fatty acids such as butanoic and hexanoic acids and methyl ketones, as well as increased levels of other compounds, have been attributed to the atypical flavour in low-fat Cheddar cheese (Carunchia-Whetstine et al 2006). They found that flavour profiles of FFC and the same FFC with the fat removed after ripening were almost identical.…”
Section: Description Profilementioning
confidence: 97%
“…The author suggests that innovations providing consumers of traditional cheese with relevant benefits are generally well accepted only if producing no substantial sensory changes. In fact, Carunchia Whetstine et al (2006) found that when fat was removed from aged full-fat Cheddar cheese, most of the flavour and flavour compounds remained in the cheese and consumers perceived the intensity of flavour in the reduced-fat cheese to be equal to the full-fat cheeses.…”
Section: Innovation Of Traditional Cheesesmentioning
confidence: 99%
“…Moreover, sensory appraisal can have a huge impact on the economic value of cheese [10, 11]. Given the subjectivity, high cost and limited repeatability of sensory evaluation, and the need to better understand its chemical and biological basis, in recent years several techniques have been used to determine the qualitative characteristics of cheese flavour compounds [1214]. Gas-chromatography combined with headspace extraction has been commonly used to investigate the link between VOC and the flavour of cheese [1517].…”
Section: Introductionmentioning
confidence: 99%